Time and time again : determination of longitude at sea in the 17th century - De Grijs, Richard, 1969- (IOP (Series). Release 4., 2017)
Determination of one's longitude at sea has perplexed sailors for many centuries. The significant uptake of world trade in the 17th and 18th Centuries rendered the increasingly urgent need to solve the 'longitude problem', an issue of strategic national importance. Historical accounts of these efforts often focus almost exclusively on John Harrison's role in 18th-Century Britain. This book starts instead from Galileo Galilei's late-16th-Century development of an accurate pendulum clock, which was first achieved in practice in the mid-17th-Century by Christiaan Huygens in the Dutch Republic. It is primarily based on collections of letters that have not been combined into a single volume before. Extensive introductory chapters on the history of map making, the establishment of the world's reference meridian at Greenwich Observatory, and the rise of the scientific enterprise provide the appropriate context for non-expert readers to fully engage with the book's main subject matter.